(untitled) (ENTHYMEMA, 2020)
Friedrich Dürrenmatt made his debut as a novelist in the 1950s, with two detective novels whose structure departs from that of more conventional thrillers and is subtly intersected by parenthetical remarks, digressions and deflections meant to break the logic of the genre and project the readers into a less rigorous and less investigable world than that of the classic enigma-novel. However, it is with a later novel, Das Versprechen (1958), that conventions are completely overturned while the investigator’s rationality no longer leads to a necessary solution and rather falls into the void of insanity and senselessness. The real Requiem for a detective novel (the subtitle of Das Versprechen), however, is represented by the short story Das Sterben der Pythia (1976), where Dürrenmatt reshapes the myth of Oedipus and makes it the epitome for every (im)possible investigation aimed to reconstruct a (the) truth in a world out of joint.